Modeling and designing for nitrogen removal in bioretention basins. (December 2021) - Wang, Jia; Chua, Lloyd H.C.; Shanahan, Peter
Abstract: The bioretention basin is a type of green infrastructure that treats stormwater runoff. However, there is a limited understanding of its treatment potential with different design configurations and limited capability to model bioretention systems. Current modeling practice fails to represent bacteria-mediated biochemical reactions that remove nitrogen. This study provides a reaction-based model of water quality treatment processes using multiple bacterial Monod kinetics under variably saturated flow conditions to predict the dynamics of nitrogen and organics in a bioretention system. The model was calibrated and validated against concentrations measured during an eight-month field monitoring program. Because the model simulates both basin hydrologic performance and biological treatment performance, it can be used to verify design guidelines by evaluating the response of the system to different design parameters. The model shows that nitrogen removal is enhanced by increasing bioretention basin volume and by setting an optimal value of hydraulic conductivity for subsurface infiltration. Graphical abstract: Image 1 Highlights: We modeled bacterially mediated biochemical transformation in a bioretention basin. We calibrated and verified the event mean effluent quality for nitrogen species. The model simulates both hydrologic and biological treatment performance. The model was used to develop performance curves to predict nitrogen removal.